VISUAL SIGNS ON THE BILLBOARD OF BALI ARTS FESTIVAL XLV YEAR 2023 : PEIRCE SEMIOTICS ANALYSIS - Gede Bayu Segara Putra; I Kadek Jayendra Dwi Putra (Institut Seni Indonesia Denpasar, 2024)
This study is aimed at examining the visual signs found on the billboard of the Bali Arts Festival XLV Year 2023 using Charles Sander Peirce's semiotics approach. In an effort to understand how messages are communicated to the audience, an analysis is conducted on the icons, indexes, and symbols that appear in the design of the billboard. Through qualitative descriptive methods, the visual elements in the billboard are separated and observed, then analyzed using Peirce's semiotics framework. The results of the analysis indicate that the theme